Pope John Paul II : Biography - Moody, John (New York, NY Park Lane, 1997)
Chronicles the life of Pope John Paul II and discusses his connections in Poland and Rome, his personal life, and how he made the choice between acting and religion
D., 8/01
Keywords: John Paul II, Pope, 1920-; Popes--Biography